PENINGKATAN PENGELOLAAN ARSIP PADA SMP NEGERI 10 PADANG - Lina Ade Yarni (Jurnal Bahana Manajemen Pendidikan, 2014)
Archival administration is the main priority for the implementation in every job as well as the archives administrasionin SMP N 10 Padang. The efforts to expedite learning process and the needsof school scape are also needed by a good archival management. The archival problem that writer discussed is based on archival management system in SMP N 10 Padang. The archival management system in SMP N 10 Padang is not appropriate with archival field and unappropriate infrastructure. In good archival management is really naaded a good attention by the principal. Based on the background, the writer is interested in discussing the archival problems with entitled “ the improving of archival management in SMP N 10 Padang”.